Predictable Returns and Non-Synchronous Trading - Fatnassi, Latifa; Abaoub, Ezzeddine (Journal of Asian Business Strategy, 2012)
The aim of this paper is to investigate non-synchronous trading effect in terms of predictability. This analysis is applied to daily and one-minute interval data on the KOREA stock market. The results indicate evidence of predictability between indices with different degrees of non-synchronous trading and when considering one-minute interval data. We then propose a simple test to infer whether such predictability is mainly attributing to non-synchronous trading or an actual delayed adjustment on part of traders. The results obtained suggest that the observed predictability is attributed to non-synchronous trading instead of delay adjustments in price to the “news”.